2003
DOI: 10.1016/s0168-6445(03)00068-8
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dehydrogenases from thermophilic and hyperthermophilic archaea and bacteria

Abstract: Many studies have been undertaken to characterise alcohol dehydrogenases (ADHs) from thermophiles and hyperthermophiles, mainly to better understand their activities and thermostability. To date, there are 20 thermophilic archaeal and 17 thermophilic bacterial strains known to have ADHs or similar enzymes, including the hypothetical proteins. Some of these thermophiles are found to have multiple ADHs, sometimes of different types. A rigid delineation of amino acid sequences amongst currently elucidated thermop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 96 publications
0
84
0
Order By: Relevance
“…The cell extract activity measurements in Table 2 suggest that this other ADH is NADPH linked and may have higher ADH activity than AdhE. It has been reported that an NADPH-linked primary ADH, AdhA, is present in the Thermoanaerobacter species and may be part of the ethanol production pathway (43,44). Sequence analysis shows that T. saccharolyticum JW/SL-YS485 has a gene (Tsac_2087) encoding an ADH that is 86% identical (at the protein level) to T. mathranii and T. ethanolicus AdhA.…”
Section: Discussionmentioning
confidence: 98%
“…The cell extract activity measurements in Table 2 suggest that this other ADH is NADPH linked and may have higher ADH activity than AdhE. It has been reported that an NADPH-linked primary ADH, AdhA, is present in the Thermoanaerobacter species and may be part of the ethanol production pathway (43,44). Sequence analysis shows that T. saccharolyticum JW/SL-YS485 has a gene (Tsac_2087) encoding an ADH that is 86% identical (at the protein level) to T. mathranii and T. ethanolicus AdhA.…”
Section: Discussionmentioning
confidence: 98%
“…Almost all are NAD(P) dependent and are classified into three different groups, the zinc-dependent ADHs, the short-chain ADHs, and the ironactivated ADHs (20). The enzyme described here, AdhD, represents a novel NAD(P)H-dependent alcohol dehydrogenase from Pyrococcus furiosus that does not show similarity with these groups but rather with the aldo-keto reductase superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol dehydrogenase (AlcDH) and aldehyde dehydrogenase (AldDH) catalyze the conversion of aldehydes to alcohols and carboxylic acids, respectively. The neighbor-joining trees of both the AlcDH and the AldDH families appear to be large and complicated (51,54). Since the experimental evidence of AlcDH and AldDH from LAB is lacking, only several putative AlcDH subfamilies and a bifunctional AlcDH/AldDH subfamily can be distinguished (data not shown).…”
Section: Enzymes Involved In the Transamination Routementioning
confidence: 99%